Mucinous adenocarcinoma with peritoneal carcinomatosis presenting as acute abdomen: a case report - Nusretoğlu, Resul; Ali, Abdullahi Khalif (Frontiers in Oncology, 2026)
BackgroundOvarian mucinous cystadenocarcinoma is a rare malignant epithelial tumor, accounting for approximately 10–15% of ovarian carcinomas. It typically presents with nonspecific abdominal symptoms and may reach a large size before detection. Presentation as an acute abdomen is uncommon and usually reflects advanced disease complicated by rupture or extensive peritoneal carcinomatosis.Case PresentationA 70-year-old postmenopausal woman presented with severe abdominal pain, vomiting, and fever. Laboratory evaluation revealed marked leukocytosis and elevated inflammatory markers. Imaging demonstrated a large multiloculated left adnexal cystic mass measuring 20 × 12 cm, associated with massive ascites and omental thickening. Due to signs of acute abdomen and clinical deterioration, urgent exploratory laparotomy was performed. Intraoperatively, diffuse peritoneal carcinomatosis and a large left ovarian mass were identified, and approximately 12 liters of mucinous fluid were drained. The patient underwent total abdominal hysterectomy with bilateral salpingo-oophorectomy, infracolic omentectomy, and appendectomy. Histopathological examination confirmed mucinous adenocarcinoma. The postoperative course was uneventful, and the patient demonstrated good recovery at six-month follow-up.ConclusionOvarian mucinous adenocarcinoma may rarely present as an acute abdomen due to extensive peritoneal involvement. Early recognition, thorough exclusion of alternative acute abdominal etiologies, accurate histopathological diagnosis, and multidisciplinary management are essential for optimal outcomes.